2018
DOI: 10.7554/elife.31670
|View full text |Cite
|
Sign up to set email alerts
|

Early alterations of social brain networks in young children with autism

Abstract: Social impairments are a hallmark of Autism Spectrum Disorders (ASD), but empirical evidence for early brain network alterations in response to social stimuli is scant in ASD. We recorded the gaze patterns and brain activity of toddlers with ASD and their typically developing peers while they explored dynamic social scenes. Directed functional connectivity analyses based on electrical source imaging revealed frequency specific network atypicalities in the theta and alpha frequency bands, manifesting as alterat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 90 publications
(134 reference statements)
1
29
0
Order By: Relevance
“…These results would suggest the presence of alterations within these areas in children with ASD while viewing the social scenes. Recently, using directed functional connectivity analyses, based on electrical source imaging, we found altered connectivity in the theta frequency band within several of the frontal and the cingulate regions while children with ASD were watching movies of biological motion (28). This would suggest that alterations in the spatio-temporal EEG microstates and the directed functional connectivity are already present at early developmental stages in ASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results would suggest the presence of alterations within these areas in children with ASD while viewing the social scenes. Recently, using directed functional connectivity analyses, based on electrical source imaging, we found altered connectivity in the theta frequency band within several of the frontal and the cingulate regions while children with ASD were watching movies of biological motion (28). This would suggest that alterations in the spatio-temporal EEG microstates and the directed functional connectivity are already present at early developmental stages in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…EEG studies have shown that an abnormal pattern of brain activity in response to faces versus objects is present early in life in ASD (2426) and that this abnormal pattern is also present in 10-month-old infants at risk for autism, suggesting that abnormality in face versus object processing is an early indicator of risk for developing ASD (27). Recently, by combining high-density EEG and eye-tracking, we found that directed functional connectivity alterations of social brain networks is a core component of atypical brain development at early stages of ASD (28, 29).…”
Section: Introductionmentioning
confidence: 99%
“…Given that connectivity algorithms take scalar time-series as their input, and as ESI outputs 3D time-series (amplitudes in the x, y, and z direction), we then determined the predominant dipole orientation for each epoch and projected the x, y, and z time-series onto this dipole to obtain a scalar time-series, in the same way that we have previously described (Coito, Michel, van Mierlo, Vulliemoz, & Plomp, 2016;Sperdin et al, 2018). Following previous work, we first computed an average dipole direction considering only the 10% strongest norms of the dipoles across time and epochs.…”
Section: Electrical Source Imaging and Selection Of Regions Of Intementioning
confidence: 99%
“…ASD is a neurodevelopmental disorder characterized by deficits in the social domain which represent hallmark early characteristics ( Sperdin et al, 2018 ). Even for simple visualization of FE, the literature is somewhat inconsistent: while some studies show group differences both in behavioral performance and neural responses, other studies show no identifiable deficits at all (for a compreensive review, see Monteiro et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%